CRITICISM OF MADRASAH HUMAN RESOURCE (HR) DEVELOPMENT ANALYSIS - Abdi, Usman; Maruhawa, Arenibi; Rambe, Syahril (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of writing this article is to find out about the criticism of Madrasah HR development analysis. This study uses a descriptive qualitative method with a literature study approach with analytical techniques based on books, journals, and documents related to the study under study. Based on the findings, it shows that Madrasah HR Development, especially for Teachers, has been running and continues to experience updates, starting from data collection using a digital or IT-based Management Information System. The current quality of madrasas is the result of collaboration in human resource development between Islamic Religious Universities, Regional Offices of the Ministry of Religion, the Director General of Islamic Education and Religious Education and Training Centers. The forms of Madrasah HR development are in the form of education, training and self-development